2022
DOI: 10.3390/nu14214510
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Immune-Enhancement and Anti-Inflammatory Effects of Fatty Acids Extracted from the Halocynthia aurantium Gonad on RAW264.7 Macrophages

Abstract: Fatty acids extracted from the Halocynthia aurantium gonad (HAGF) were shown to be primarily composed of the highest concentrations of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) at 41% and 17% of total fatty acids, respectively. In the present study, HAGF were examined for their immunostimulant and anti-inflammatory effects on RAW264.7 macrophage cells. HAGF were found to significantly boost nitric oxide (NO) production and increase the levels of Inducible nitric oxide synthase (iNOS), cyclooxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Macrophages and monocytes respond to pathogens in a highly variable manner depending on the nature of the pathogen and the contextual setting of the encounter [24,26]. In this study, we focused on LPS tolerance, a form of trained immunity that aims to protect the host from overproduction of inflammatory mediators [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages and monocytes respond to pathogens in a highly variable manner depending on the nature of the pathogen and the contextual setting of the encounter [24,26]. In this study, we focused on LPS tolerance, a form of trained immunity that aims to protect the host from overproduction of inflammatory mediators [2].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that DHA mediates anti-inflammatory effects in LPS-stimulated macrophages [24,25]. We therefore addressed whether DHA would interfere with the induction of LPS tolerance in monocytes and polarized M (IFNγ) and M (IL-4) macrophages.…”
Section: Dha Does Not Affect Lps Tolerancementioning
confidence: 98%